f-x-ln-x-x-1-e-f-x-x-dx-1-e-ln-f-x-x-dx- Tinku Tara June 3, 2023 Integration 0 Comments FacebookTweetPin Question Number 933 by 123456 last updated on 29/Apr/15 f(x)=lnxx∫e1f(x)xdx=?∫e1lnf(x)xdx=? Commented by prakash jain last updated on 30/Apr/15 ∫lnxx2dx=lnx⋅−1x+∫1x2dx=−lnxx−1xlimitsfrom1toe,−1e−1e+1=1−2e Terms of Service Privacy Policy Contact: info@tinkutara.com FacebookTweetPin Post navigation Previous Previous post: find-f-a-b-0-cos-ax-cos-bx-x-2-a-2-x-2-b-2-dx-with-a-gt-0-and-b-gt-0-2-calculate-0-cos-x-cos-2x-x-2-1-x-2-4-dx-Next Next post: calculate-I-n-0-dx-x-n-3-2-with-n-gt-1- Leave a Reply Cancel replyYour email address will not be published. Required fields are marked *Comment * Name * Save my name, email, and website in this browser for the next time I comment.